Kinematic Analysis of Combined Suture-Button and Suture Anchor Augment Constructs for Ankle Syndesmosis Injuries. (April 2020) - Wood, Addison R.; Arshad, Seyed A.; Kim, Hannah; Stewart, Donald
Background: Syndesmosis injuries are common, with up to 25% of all ankle injuries being reported to involve an associated syndesmosis injury. These injuries are typically treated with cortical screw fixation or suture-button implants when indicated, but the addition of a suture anchor augment implant has yet to be evaluated. The purpose of this study was to evaluate the ability of a suture anchor augment to add sagittal plane translational and transverse plane rotational constraint to suture-button constructs with syndesmosis injuries. We hypothesized that the suture anchor augment oriented in parallel with the fibers of an injured anterior-inferior tibiofibular ligament (AITFL) in addition to a suture-button construct would achieve physiological motion and stability at the syndesmosis through increased rotational and translational constraint of the fibula. Methods: Eleven fresh-frozen cadaver ankles were stressed in external rotation using a custom-made ankle rig. Each ankle had simultaneous recording of ultrasound video, 6 degrees-of-freedom kinematics of the fibula and tibia, and torque as the ankle was stressed by an examiner. The ankles were tested in 6 different states: native uninjured; injured with interosseous ligament and AITFL sectioned; 1× suture button; 2× suture buttons, divergent; 1× suture anchor augment with 2× suture buttons, divergent; and 1× suture anchor augment with 1× suture buttons. Results: Only the suture anchor augment + 2× suture buttons and suture anchor augment + 1× suture-button constructs were found to be significantly different from the injured state ( P = .0003, P = .002) with mean external rotation of the fibula. Conclusion: Overall, the most important finding of this study was that the addition of a suture anchor augment to suture-button constructs provided a mechanism to increase external rotational constraint of the fibula. Clinical Relevance: This study provides a mechanistic understanding of how the combined suture-button and suture anchor augment construct provides an anatomically similar reconstruction of constraints found in the native ankle. However, none of the constructs examined in this study were able to fully restore physiologic motion.